Methane emissions from elements of gas distribution networks and the energy security of EU countries in time of gas wars - Skrzyński, Tomasz; Narloch, Piotr (Polityka i Społeczeństwo, 2023)
The scale of methane emissions from gas distribution systems has serious consequences for energy security, ensuring the security of natural gas transmission and reducing gas losses in transport. That is why it is important to determine the scale of such emissions from individual elements of the infrastructure. It has been confirmed that such emissions have a significant effect on the military security of EU countries. The emission factor (EF) is affected by many other causes. The best method of calculating the EF is one that takes into account the most variables. A theoretical method of determining the EF has been developed, taking into consideration the age of the equipment as well as pressure, temperature and speed. When comparing the methods in the literature to date, one has to bear in mind that none of them describes the variables that affect the magnitude of the EF. To map an actual emission, it is crucial to have data that describe the gas infrastructure component under analysis, along with the most precise information available to characterise the operating conditions.